Association of Social Support and Family Environment with Cognitive Function in Peritoneal Dialysis Patients. Issue 1 (January 2017) - Wang, Qin; Yang, Zhi-Kai; Sun, Xiu-Mei; Du, Yun; Song, Yi-Fan; Ren, Ye-Ping; Dong, Jie
Background: Cognitive impairment (CI) is a common phenomenon and predictive of high mortality in peritoneal dialysis (PD) patients. This study aimed to analyze the association of social support and family environment with cognitive function in PD patients. Methods: This is a cross-sectional study of PD patients from Peking University First Hospital and the Second Affiliated Hospital of Harbin Medical University. Global cognitive function was measured using the Modified Mini-Mental State Examination (3MS), executive function was measured by the A and B trail-making tests, and other cognitive functions were measured by the Repeatable Battery for the Assessment of Neuropsychological Status. Social support was measured with the Social Support Scale developed by Xiaoshuiyuan and family environment was measured with the Chinese Version of the Family Environment Scale (FES-CV). Results: The prevalence of CI and executive dysfunction among the 173 patients in the study was, respectively, 16.8% and 26.3%. Logistic regression found that higher global social support (odds ratio [OR] = 1.09, 1.01 – 1.17, p = 0.027) and subjective social support predicted higher prevalence of CI (OR = 1.13, 1.02 – 1.25, p = 0.022), adjusting for covariates. Analyses of the FES-CV dimensions found that greater independence was significantly associated with better immediate memory and delayed memory. Moreover, higher scores on achievement orientation were significantly associated with poorer language skills. Conclusions: Our findings indicate that social support is negatively associated with the cognitive function of PD patients and that some dimensions of the family environment are significantly associated with several domains of cognitive function.